Assessment of nursing informatics competency level among bedside nurses in Prince Mohammed bin Abdul-Aziz Hospital, Riyadh, Saudi Arabia - Melhem, Sofyan Ibrahim Hussein Bani (2025)
Advanced clinical technology is widely used by nurses in today's healthcare settings, requiring the possession of sufficient informatics knowledge and skills. Nursing competency in this field is now essential, considering the increasing focus on patient safety and care quality through informatics. The purpose of this research is to evaluate the level of Nursing Informatics (NI) competency and determine the factors influencing this competency among bedside nurses in Prince Mohammed bin Abdul-Aziz Hospital (PMAH). The study adopts a descriptive, correlational, cross-sectional approach involving 196 nurses at PMAH. Utilizing the Nursing Informatics Competency Assessment Tool (NICAT), developed by Alphonsa Rahman in 2015, the research assesses bedside nurses' informatics competency. Additionally, the questionnaire gathers demographic data. The data was entered into SPSS 25 software, and correlation analysis was carried out. The average level of competency across all categories was significantly tilted toward 'Competent, Very Competent, and Expert' (74%), with a substantially lower percent in 'Novice or Advanced Beginner' (26%). Educational level was identified as significantly correlated with the level of nursing informatics competency (NIC) (P = 0.047). However, age, gender, years of nursing experience, and use of the health information system showed no significant correlation with NIC level. These findings underscore the significance of nursing informatics competency within healthcare organizations, as it determines nurses’ ability to effectively utilize available health information systems, thereby enhancing healthcare quality and improve patient safety.